1975
DOI: 10.1148/114.1.225
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Ehrlich Ascites Tumor Using Intraperitoneal Colloidal198Au

Abstract: Previous work has shown that radioactive colloids can cure Ehrlich ascites tumor. In this experiment, the dose of colloidal 198Au needed has been correlated with the number of tumor cells inoculated. On Day 1, varying numbers of Ehrlich cells (10(2), 10(3), 10(4), 10(5), 10(6)) were injected intraperitoneally into 310 BALB/c male mice. Two hours later, varying doses (10, 20, 40, 80, and 160 muCi) of 198Au were injected intraperitoneally. Controls were injected with normal saline. Generally, the lower cell inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…3335 Other than arthritis, radioisotopes of gold have also found wide application in the regional treatment of different types of cancer. 3639 All these previous work using gold for cancer or arthritis therapy was based upon local injection which inevitably limits the application and efficacy of gold based treatment. Through the method reported in this work, gold particles with therapeutic potential for arthritis or cancer could be engineered for specific targeting of disease tissues and, hence, could be introduced systemically in the circulatory system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3335 Other than arthritis, radioisotopes of gold have also found wide application in the regional treatment of different types of cancer. 3639 All these previous work using gold for cancer or arthritis therapy was based upon local injection which inevitably limits the application and efficacy of gold based treatment. Through the method reported in this work, gold particles with therapeutic potential for arthritis or cancer could be engineered for specific targeting of disease tissues and, hence, could be introduced systemically in the circulatory system.…”
Section: Resultsmentioning
confidence: 99%
“…Other than imaging, targeted delivery of GdNPs could also contribute to enhanced arthritis therapy in light of established benefits of gold treatment in inflammatory arthritis. In many previous studies, positive findings have been reported for clinical uses of gold compounds in the treatment of rheumatic diseases including psoriasis, juvenile arthritis, palindromic rheumatism, and discoid lupus erythematosus. Other than arthritis, radioisotopes of gold have also found wide application in the regional treatment of different types of cancer. All of these previous works using gold for cancer or arthritis therapy were based upon local injection, which inevitably limits the application and efficacy of gold-based treatment. Through the method reported in this work, gold particles with therapeutic potential for arthritis or cancer could be engineered for specific targeting of disease tissues and, hence, could be introduced systemically in the circulatory system.…”
Section: Resultsmentioning
confidence: 99%
“…4 Colloidal solutions of the 198 Au gold isotope (half-life time, 65 h) were therapeutically successful at cancer care facilities. 5 More recent examples of colloidal gold applications include catalytic processes and electron transport in biomacromolecules, 6 transport of substances into cells by endocytosis, 7 investigation of cell motility, 8 and improvement of PCR efficiency. 9 Despite the centuries-old history, a ''revolution in immunochemistry,'' 10 associated with the use of gold particles in biological research, took place in 1971, when British researchers W. P. Faulk and G. M. Taylor published an article titled ''An immunocolloid method for the electron microscope.''…”
Section: Nikolai Khlebtsovmentioning
confidence: 99%
“…Another advantage of using 198 Au is its short half-life and it does not require removal of the radio source (157). The use of radiogold is very efficient; it has a 96.3 % patient survival rate for the treatment of stage Ia ovarian cancer (158, 159). Radiogold has also been used in the treatment of hepatic carcinoma and endometrial cancer with minimal side effects compared to traditional radiotherapy (7).…”
Section: Use Of Radioisotopes Of Colloidal Goldmentioning
confidence: 99%